Dampak Capital Structure, ROE, CR, dan Peluang Pertumbuhan Terhadap Firm Value Perusahaan Jasa Di BEI - Tri Hartiningsih (Akademi Akuntasi Effendiharahap, 2023)
The aims of this research is to examine the effect of managerial ownership, insitutisional ownership, dividend policy, and debt policy on firm value by including the variable size, growth and performance as the control variable (study at Manufacturing Companies Lisyting in Indonesian Stock Exchange since 2007 until 2009 period. The population in this study are all manufacturing companies listed on the Ondonesian Stock Exchange from 2007 until 2009 period. The sample in this study is manufacturing company according to the criteria established. Regression analysis was performed with based on the results of data analysis this study concludes some of the following: (1) Variable managerial ownershipis proven to affects the firm value, 2) Institutional ownership variable is not proven to affect the value of the company, (3) Dividend policy is not proven to affect the value of the company, (4) Debt policy not proven to effect on firm value (5) The size of the company is proved positive effect on firm value, (6) The growth of the company proved to affect the value of the firm (7) The performance of the company proved possitive to effect firm value.